Reperfusion and Clinical Outcomes in Acute Ischemic Stroke: Systematic Review and Meta-Analysis of the Stent-Retriever-Based, Early Window Endovascular Stroke Trials - Manning, Nathan W.; Warne, Charles D.; Meyers, Philip M. (Frontiers in Neurology, 2018)
Objective: To explore the effects of reperfusion grade rates on clinical outcomes in the setting of stent-retriever based reperfusion therapy for anterior circulation stroke in early time windows. Methods: Systematic searching of Medline and Embase databases was performed to identify stroke trials of stent-retriever based therapy versus standard care. Mixed effects meta-regression was used to analyse the trial-level association between reperfusion rates and clinical outcomes. Results: A total of five trials met the inclusion criteria (n = 1287). Rates of successful reperfusion (mTICI 2b/3) demonstrated strong evidence for an association with good functional outcomes (mRS 0-2) OR 1.59 [95% CI 1.16, 2.19] p=0.019 and very strong evidence for an association with excellent functional outcomes (mRS 0-1) OR 2.10 [95% CI 1.46, 3.01] p=0.007. In addition there was weak evidence for an association with symptomatic intracranial haemorrhage OR 0.54 [95% CI 0.28, 1.04] p=0.057 and mortality OR 0.69 [95% CI 0.69, 1.01] p=0.053. Conclusion: In early, stent-retriever based acute ischaemic stroke treatment, reperfusion appears to be a major predictor of outcomes. Every 10% increase in the rates of successful reperfusion is associated with an 11% increase in the probability of achieving good and 17% increase in the probability of achieving excellent outcomes. Symptomatic intracranial haemorrhage and mortality may be decreased as reperfusion rates are improved.